Making a Microaggression: Using Big Data and Qualitative Analysis to Map the Reproduction and Disruption of Microaggressions through Social Media. (November 2020) - Eschmann, Rob; Groshek, Jacob; Chanderdatt, Rachel; Chang, Khea; Whyte, Maysa
Racial microaggressions are defined as subtle racial slights that can be offensive or hurtful. One of the defining characteristics of racial microaggressions is how difficult they can be to respond to, and the literature reports that not responding may be the most common response to microaggressions. This study addresses a vital gap in the existing literature by examining the extent to which the silence that characterizes face-to-face experiences with microaggressions extends into online social media spaces. Drawing on a dataset of 254, 964 tweets over an 8-year period, we present and examine trends in the usage of the term "microaggressions" over time. Furthermore, we then generate a purposive sample of 1, 038 of the most influential tweets to explore discussions and content themes through an in-depth qualitative analysis of these messages. Here, we find both a drastic increase in the usage of the term microaggression on Twitter over time and an intense contestation over its meaning and repercussions for both individuals and society. Implications of these findings in understanding the role of online social media discourse in challenging or reproducing hegemonic racial structures is discussed.